Membangun Loyalitas Dengan Kepercayaan dan Kualitas Layanan Melalui Kepuasan Pelanggan - Rosalina, Ulfa; Tamamudin, Tamamudin (JIEF : Journal of Islamic Economics and Finance, 2021)
The purpose of this study was to identify and analyze the influence of the level of trust and service quality on customer loyalty with customer satisfaction as a mediating variable at PT. Fairus Permata Mulia Pekalongan. The population in this study amounted to 927 worshipers with a sample of 90 worshipers and the sampling technique used random sampling techniques. The method of collecting data through a questionnaire. The data analysis technique used is Path Analysis. The results showed that the level of trust and service quality had a direct effect on customer satisfaction. The level of trust has no direct effect on customer loyalty, while service quality and customer satisfaction have a direct effect on customer loyalty. Customer satisfaction is able to play a role as a mediating variable between the level of trust and service quality on customer loyalty to the Umrah pilgrims of PT. Fairus Permata Mulia Pekalongan.